The Effect of the PBL Model through the CTL Approach to the Achievement in Learning Social Sciences - Fajar Surya Hutama (Pascasarjana UM, 2014)
Pengaruh Model PBL melalui Pendekatan CTL terhadap Hasil Belajar IPSAbstract: This research was aimed to know is any difference regarding the learning achievements between the class with the PBL model through the CTL approach and the class with conventional model in the teaching and learning of Social Sciences. The research design is used in this study was the quasi-experimental design, particularly the nonequivalent control-group design. The learning achievements of the class in which the model was implemented show a better result than the one with the conventional model in the teaching and learning of Social Sciences. The difference is shown by the significantly increased mean of scores of the experimental class, compared with the control group which did not experience a similar significant increase. Key Words: the PBL model through the CTL approach, learning achievements Abstrak: Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar antara kelas yang menggu-nakan model PBL melalui pendekatan CTL dengan kelas yang menggunakan model pembelajaran konvensional dalam pembelajaran IPS. Desain yang digunakan dalam penelitian ini adalah desain quasi experimental dengan bentuk nonequivalent control group design. Hasil penelitian menunjuk-kan bahwa hasil belajar kelas yang menggunakan model PBL melalui pendekatan CTL lebih baik di-bandingkan dengan kelas yang menggunakan model pembelajaran konvensional dalam pembelajaran IPS. Perbedaaan peningkatan hasil belajar yang signifikan terlihat dari nilai rata-rata kelas yang menggunakan model PBL melalui pendekatan CTL, sedangkan pada kelas yang menggunakan model pembelajaran konvensional peningkatannya tidak terlalu signifikan.Kata kunci: model PBL melalui pendekatan CTL, hasil belajar